Teacher attachment styles and the management of insecurely attached Foundation Phase learners - Klug, Karin Lee (University of the Witwatersrand, Johannesburg, 2025)
Research has focused on how teacher-learner relationships can impact on learners’ overall well-being and affect their academic success at school. Despite the clear importance of the teacher-learner relationships, little research has focused on the quality of relationships between teachers and learners especially in the Foundation Phase (Grades 0-3) in South Africa. Moreover, very few studies have explored how teachers’ attachment styles affect the way they relate to and manage learners in the classroom. This study hoped to contribute to this gap in the literature on middle childhood, investigating the relationship between primary school teachers’ attachment styles and the various ways they report managing and responding to challenging children in the Foundation Phase of primary school. It is hoped that this will inform understandings of the reportedly poor relationships between teachers and learners in South Africa. This was done from the perspective of attachment theory, using a concurrent mixed methods approach to explore teachers’ attachment styles, their discipline styles, and their responses to learners with insecure attachment presentations. Although findings revealed no statistically significant differences between securely and insecurely attached teachers with regards to discipline and classroom management styles, and responses to the different presentation of insecure learners, likely due to the small sample size, trends with regards to differences in these areas were identified via the analysis of the qualitative data. Most teachers were tolerant and empathic towards anxious-ambivalent learners and managed anxious-avoidant learners with sensitivity, reflecting their understanding of this child. Teachers showed the least compassion and tolerance towards anxious-frightened or disorganised learners. Most teachers were able to manage learners who presented with similar traits as their former younger selves with sensitivity and compassion. However, it appeared that teachers who are insecure in both childhood and adulthood may be intolerant of learners who present with a similar childhood attachment, until experience as a teacher affords them the opportunity to gain experience and adjust their behaviour. Although both securely and insecurely attached teachers self-reported authoritative classroom management styles, the securely attached teachers could relate to the authoritarian statement of discipline to a greater degree than the insecurely attached teachers. However, to substantiate any claims about the relationship between teachers' attachment styles and their management of insecurely attached learners, these findings will need to be verified using larger samples. It is however evident that teachers would benefit from training in how to identify the differently insecurely attached learners in their classes and be empowered with the tools on how to deal with difficult to manage learners. It is further recommended that student teachers be exposed to the knowledge and skills of attachment theory before they embark on their practical teaching experiences in order to bridge the gap between theory and practice.
A Dissertation submitted in fulfilment of the requirements for the degree of Master of Arts by Dissertation (in the field of Psychology) in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2025
Keywords: Attachment Theory; Discipline styles; Classroom management; Secure attachment; Insecure attachment; UCTD; SDG-4: Quality education; SDG-10: Reduced inequalities